POLA PENGUJIAN PERANGKAT SR4: KOMPONEN LOOP AKTUASI INSTRUMENTASI REAKTOR KARTINI - Achmad Suntoro (Jurnal Perangkat Nuklir, 2013)
It has been set-up a set of evaluation tests for SR4 equipment after some components of the equipment have been fabricated and or renovated. SR4 is an equipment as parl of the Karlini nuclear reaktor instrumentation. The evaluation test scheme implemented utilized the modification for testing of installation and construction of instrumentation in nuclear reactor. The evaluation test has been grouped into three categories: installation cable test, component level test before installation, and module in the sub-rack of equipment test. Electrical and electronic principles are to be used in considering of testing types because SR4 equipment is mainly electronic system. This evaluation test scheme has been implemented to the SR4 equipment so that the SR4 equipment is ready to be used as in its specifications.  Telah dibuat paket-paket uji untuk perangkat SR4 setelah komponen perangkat tersebut difabrikasi dan atau diremajakan. SR4 adalah salah satu perangkat dalam instrumentasi reaktor Karlini. Pola pengujian yang dilaksanakan menggunakan pola instalasi dan konstruksi dalam instrumentasi reaktor nuklir yang dimodifikasi untuk proses pengujian. Pengujian dikelompokkan dalam tiga kelompok: instalasi pengkabelan, komponen sebelum dipasang, dan modul dalam subrack. Teknik elektronika dan kelistrikan menjadi dasar pemikiran penentuan jenis uji, karena perangkat SR4 didominasi oleh rangkaian elektronik. Pola pengujian ini telah dijalankan pada perangkat SR4 agar perangkat tersebut siap digunakan sesuai dengan spesifikasi disainnya